2015
DOI: 10.1007/s00542-015-2620-6
|View full text |Cite
|
Sign up to set email alerts
|

Microwave atomic force microscope: MG63 osteoblast-like cells analysis on nanometer scale

Abstract: combinations of proteins, carbohydrates, lipids and nucleic acids. These compositions carry out complicated biochemical and physiological process inside the cell. To study these complicated process, acquiring the morphological and fundamental function of these intracellular structures become an indispensable process.With the development of biotechnology, more and more approaches have been developed to investigate the intracellular structures. Immunofluorescence staining was the most widely used method to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The results of the AFM studies are depicted in Figure 12a-f. The 2D AFM images highlighted that on the surface of the investigated thin films, typical patterns of cellular morphology of MG63 (ATCC CRL1427) cells having typical spindle-like shapes were found [49,50]. More than that, the data also suggested that the MG63 (ATCC CRL1427) cells had a good adherence to the samples and proliferated on the surfaces of the HAp, 0.05 AgHAp and 0.1 AgHAp thin films.…”
Section: Resultsmentioning
confidence: 80%
“…The results of the AFM studies are depicted in Figure 12a-f. The 2D AFM images highlighted that on the surface of the investigated thin films, typical patterns of cellular morphology of MG63 (ATCC CRL1427) cells having typical spindle-like shapes were found [49,50]. More than that, the data also suggested that the MG63 (ATCC CRL1427) cells had a good adherence to the samples and proliferated on the surfaces of the HAp, 0.05 AgHAp and 0.1 AgHAp thin films.…”
Section: Resultsmentioning
confidence: 80%
“…It realizes the automatic loading and unloading of scanned samples through a manipulator. The AFM indirectly realizes the automatic replacement of the AFM scanning probe by replacing the probe holder equipped with the scanning probe [4].…”
Section: Introductionmentioning
confidence: 99%